Avaliação de diferentes métodos para detecção de sinergismo antimicrobiano em amostras de Klebsiella pneumoniae produtora de KPC-2 - Alves, Jânio Leal Borges (2015)
The increase in drug-resistant bacteria and the low development of new antibiotics represent a big challenge of treatment of multiresistant bacterial infections. In this context the antibacterial association has been an alternative in the better search results. The in vitro evaluation of synergistic action has been evaluated by different methodologies that are complex and laborious. The objective of this study was propose easily antimicrobial synergism methods and compare it with different detection methods already established in the literature, using meropenem, gentamicin and polymyxin B against positive and negative isolates of blaKPC-2 Klebsiella pneumoniae. Eight K. pneumonia strains were tested to the standard synergy methods: time-kill curve (TKC) and checkerboard (CB) and compared to the proposed methodologies double disc (DD) and time-kill curve modified (TKCM) and to the also described in literature E- Test® Cross 90º (C90º), E-Test® fixed ratio (FR) and disk approximation (DA) methods. There was not a direct relation between the results obtained by standard methods CB and TKC. None of the E-test e disc methods showed good correlation with TKC or CB. In relation to the proposed methods in this study, the best who correlation with CB and TKC method, was the TKCM with 66.7% and 42.9% agreement and 90% and 83% sensitivity respectively. Considering the data observed in this study, the antimicrobial associations tested (PB +MR, PB +GN and GN+MR), we conclude that the methodologies based on E-test® and disk diffusion are ineffective in the detection of synergism. Furthermore, it was found that the TKCM method proved to be sensitive and rapid of synergism detection and can be easily implemented in a routine laboratory.